2011
DOI: 10.1159/000322475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise and Respiratory Training on Clinical Progression and Survival in Patients with Severe Chronic Pulmonary Hypertension

Abstract: Background: Even though specific agents for the treatment of patients with pulmonary hypertension (PH) are available, in PH patients, physical capacity and quality of life (QoL) are often restricted and survival is reduced. Objectives: This study prospectively investigated the long-term effects of respiratory and exercise training in patients with severe chronic PH regarding safety, time to clinical worsening and survival. Methods: Fifty-eight consecutive patients with severe PH on stable disease-targeted medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
179
3
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(211 citation statements)
references
References 67 publications
8
179
3
21
Order By: Relevance
“…The patient in this study had a 50 per cent reduction in his dyspnoea, going from 4 to 2, a situation that completely changes the outlook regarding the appearance of symptoms during the performance of activities of daily living. There were benefits in the functional classification of the WHO, starting in class III and ending in class II, which is similar to that found by Ehlken et al, 30 who in a clinical trial found in 3 weeks of training significant improvements in the functional class of 2.8±0.6 to 2.4±0.5; however, although in this and in Grunig's study 31 there was a decrease in the average classification score, it could not be established if they changed the grade from one stage to another, as it does in the case reported by us.…”
supporting
confidence: 90%
“…The patient in this study had a 50 per cent reduction in his dyspnoea, going from 4 to 2, a situation that completely changes the outlook regarding the appearance of symptoms during the performance of activities of daily living. There were benefits in the functional classification of the WHO, starting in class III and ending in class II, which is similar to that found by Ehlken et al, 30 who in a clinical trial found in 3 weeks of training significant improvements in the functional class of 2.8±0.6 to 2.4±0.5; however, although in this and in Grunig's study 31 there was a decrease in the average classification score, it could not be established if they changed the grade from one stage to another, as it does in the case reported by us.…”
supporting
confidence: 90%
“…Exercise training also improved peak oxygen consumption and World Health Organization (WHO) functional class [1], and possibly the clinical outcome, with 1-and 2-yr survival rates of 100 and 95%, respectively [4]. Importantly, no severe adverse events occurred in the previously assessed training groups.…”
mentioning
confidence: 87%
“…[45], при этом не было выявлено отрицательного влияния физических тре-нировок на внутрисердечную гемодинамику, которая контролировалась инвазивными методами исследова-ния. В настоящее время вопрос физических трениро-вок у больных с легочной гипертензией продолжает активно изучаться [46][47][48][49], хотя часто и без привлече-ния ЭхоКГ методов исследования ПЖ. Нагрузочная допплер-ЭхоКГ для проведения скрининга легочной гипертензии не рекомендована из-за отсутствия доста-точной доказательной базы и утвержденных критериев диагностики [42].…”
Section: этнические и региональные особенности структуры и функции пжunclassified